Research on the Prediction of Euro Pound Exchange Rate Based on ARIMA Model - Yang, Yaojun (BCP Business & Management, 2022)
There have been many changes in the macroeconomy in recent years, both in the UK and in Europe. With the different global situations, the Pounds against euro is constantly being affected. This paper uses the ARIMA model as the main model to forecast the Euro Pound exchange rate for the next eight years. The results shows that it fluctuates slightly from 2022 to 2026, rises from 2026, reaches a peak of about 0.9 in the middle of the same year for the next eight years and then gradually declines, before suddenly and sharply falling to about 0.76 in 2030.This result is informative and helpful to users of both the Euro and the Pound to some extent. In turn, it is of great significance to the country in stabilising the foreign exchange market and preventing potential financial risks arising from a significant reduction in foreign exchange rates.